The Effect of Giving Red Dragon Fruit (Hylocereus polyrhizus) and Red Bean Yogurt (Phaseolus vulgaris L.) on The Satiety Index in Obese Adolescents - Yenni Oktora; Harsono Salimo; Lilik Retna Kartikasari (Nusantara Science and Technology Proceedings, 2022)
The oligosaccharide content of red dragon fruit shows prebiotic properties as nutrients for the growth of probiotic bacteria in yogurt, as well as provides the additional substrate to increase probiotic activity reaching the large intestine so that it affects appetite regulation caused by gastric emptying rates and increased postprandial amino acids. The purpose of this study was to analyze the effect of giving red dragon fruit and red bean yogurt to the satiety index in 60 obese adolescents for 14 days, who live in Mataram City, West Nusa Tenggara Province. Research respondents were divided into five groups with each group consisting of 12 people. In the control group (K), group P1 was given 70 g of red dragon fruit and 169 ml of red bean yogurt, group P2 was given 140 g of red dragon fruit and 113 ml of red bean yogurt, and group P3 was given 210 g of red dragon fruit and 57 ml of red bean yogurt, group P4 was only given 280 g of red dragon fruit. This research was an experimental trial with a randomized controlled trial design, pre-post test design with control group design. Appetite levels including hunger, satisfaction, and desire to eat were evaluated using the Visual Analogue Scale (VAS). Normality test using Kolmogorov-Smirnov test. Statistical analysis using Paired-t-test, Wilcoxon, and One Way Anova with a significant value of p <0.05. There was a difference in the satiety index between the 4 treatment groups at 0, 30 and 120 minutes (p <0.05) and there was no significant difference at the 60th minute. and 90 (p>0.05). Meanwhile, the control group compared to the 4 treatment groups showed that there was a significant difference in satiety index (p<0.05). Giving red dragon fruit and red bean yogurt resulted in a different satiety index at 0, 30, and 120 minutes compared to the control group.